Pandangan Buddhisme Tentang Peran Wanita - Sapardi Sapardi (STABN Sriwjaya, 2020)
This research is important to do to find out why the role of women is important. A woman is the foundation for the creation of a strong young generation. According to Buddhist teachings, that being born as a human and being able to live in a suitable place, together in society in the quest for an honorable life becomes a gift and a blessing (manggala). In the phenomenon of globalization and the advancement of modern science with various problems that occur, there is a tendency for women not to understand the role of women as the main foundation in creating a strong family.In the perspective of the role of women, human physical health becomes a very important agent in continuing the process of life. Therefore, the important role of a woman's health must be a concern. Related to this, it is necessary to study how the views of a woman's physical health according to Buddhism. Cause and effect related to the role of a woman in her life. In this study, theories related to health theory and Buddhist theories are juxtaposed on the importance of a woman's physical health, in addition to mental health.To prepare for the analysis, research data was collected by identifying the texts from the Tipitaka/Tripitaka Scriptures and the Commentaries that were related to the main problem. After the data is collected, it is processed, analyzed and dissected using several theories, including: the importance of a woman's physical health, hermeneutics, and causal relationships (paticcasamuppada). These theories were used to compile a scientific study of the importance of women's physical health according to Buddhism.